THE EFFECT OF PRECURSOR-ACTIVATOR RATIO AND ACTIVATOR TYPE ON THE BULK DENSITY, COMPRESSIVE STRENGTH, AND MICROSTRUCTURE OF ABUAN PUMICE-BASED GEOPOLYMER BINDER - Dewa Ayu Anggitha Pitaloka; I Made Alit Karyawan Salain; Ida Bagus Rai Widiarsa (Jurnal Ilmiah Teknik Sipil, 2024)
This research developed a geopolymer binder based on pumice waste from Abuan Village, Kintamani, which is rich in silica and alumina, with a composition of SiO₂ 55.90%, Al₂O₃ 12.00%, CaO 6.25%, and other metals around 8.61%. The activators used are Na₂SiO₃ combined with either NaOH or KOH at a concentration of 12 M, with precursor-activator (P/A) ratios of 75%:25%, 70%:30%, and 65%:35% and an alkali ratio of NS/NH at 2:1. Cube samples 50 x 50 x 50 mm were analyzed to measure bulk density and compressive strength at 7, 14, and 28 days after being cured in an oven at 80°C for 72 hours. The bulk density test results for samples using NaOH showed an increase as the P/A ratio increased, but a decrease as the testing age increased. Then, the bulk density results for KOH samples showed the opposite trend both in terms of P/A ratio and age. The average compressive strength test for NaOH samples increased with the P/A ratio, and while it fluctuated by age, it continued to increase overall. The KOH samples followed a similar trend in P/A ratio but tended to decrease over time. This behavior is influenced by the chemical and physical properties of the activators used. Microstructural analysis was conducted using X-Ray Diffraction (X-RD) on the samples with the lowest and highest compressive strength. New minerals formed in NaOH samples, including Sodium Aluminosilicate, Albite, and Anorthite, while KOH samples showed formations of Dipotassium Sulfate (VI) – Alpha, Ht, Albite, and Cristobalite.